Vaccination of healthcare workers to protect patients at increased risk of acute respiratory disease: summary of a systematic review. (27th August 2013) - Dolan, Gayle P.; Harris, Rebecca C.; Clarkson, Mandy; Sokal, Rachel; Morgan, Gemma; Mukaigawara, Mitsuru; Horiuchi, Hiroshi; Hale, Rachel; Stormont, Laura; Béchard‐Evans, Laura; Chao, Yi‐Sheng; Eremin, Sergey; et al.
Abstract : Healthcare workers (HCWs) are at increased risk of exposure to respiratory pathogens and may transmit infection to vulnerable patients. This study summarises a recent systematic review, which aimed to assess evidence that influenza or pneumococcal vaccination of HCWs provides indirect protection for those patients most at risk of severe or complicated acute respiratory infection. A number of healthcare databases and sources of grey literature were searched using a predefined strategy, and citations screened for eligibility in accordance with specified inclusion criteria. Risk of bias was assessed using validated tools and results summarised qualitatively. Twenty papers were included in the final review, all of which considered influenza vaccination of HCW. As such, planned subanalysis of pneumococcal vaccination was discarded. The majority of primary research studies included (11/14) were conducted in long‐term care facilities, but there was marked heterogeneity in terms of the population, intervention/exposure and outcomes considered. Consistency in the direction of effect was observed across several different outcome measures, suggesting that influenza vaccination of HCWs is likely to offer some protection. Further evidence is, however, required from acute care settings.